Development of a rapid DNA screening procedure for the Factor V Leiden mutation. Issue 6 (December 1996) - Scobie, G A; Ho, S T; Dolan, G.; Kalsheker, N A
Abstract : Aim —To develop a rapid, simple and highly specific DNA screening procedure based on the amplification refractory mutation system (ARMS) to detect the Leiden mutation in whole blood. Methods —ARMS PCR amplification primers with additional mismatches at either -2 or -3, which greatly improves specificity, were constructed to detect the normal Factor V gene and the Leiden mutation in whole blood samples from patients with abnormal clotting results. Results —Construction of ARMS primers with either an additional mismatch at -2 or -3 at the 3′ end of the primer could be used to detect the Leiden mutation in 0.5 μ1 whole blood in under three hours. Primers destabilised at position -3 could be used at a lower annealing temperature, which gave greater sensitivity and are now routinely used. A control set of primers was included in the same reaction to act as a positive control. Conclusions —This rapid and specific assay for the factor V Leiden mutation is a useful addition to the investigation of patients with or at risk from thrombovascular disease.